The Future of the Scan Room: Will AI Replace Medical Imaging Technicians? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid advancement of Artificial Intelligence AI in healthcare has sparked a critical debate across medical specialties. Perhaps nowhere is this discussio...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care